Characterization of a population of Helicotylenchus Dihystera (cobb, 1893) Sher, 1961, parasitizing maize roots, in Southern Córdoba, Argentina - Brücher, Elsa (2019)
Helicotylenchus are root parasites of cultivated and noncultivated plants. Species identification can be difficult because the nematode shares several diagnostic characters and exhibits an important interspecific variability. Species recognition is essential for planning appropriate control strategies or preventing the spread of these nematodes to other areas. In this work, morphological and morphometric characters from a single population were evaluated. Molecular analysis of D2-D3 of the 28s-rDNA and the 5.8s-ITS2 regions by PCR generated two new sequences that were deposited in Genbank. In addition, identification of the species was supported by phylogenetic analysis using Bayesian inference. This work is the first morphological, morphometric, and molecular characterization of a H. dihystera population from Argentina.